EPISTEMOLOGI PENDIDIKAN ISLAM NUSANTARA (Studi Interpretatif-Simbolik atas Peran Kampus, Pesantren dan Lembaga Adat) - Hamsyah, Junaidi (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE EPISTIMOLOGY OF ARCHIPELAGO ISLAMIC EDUCATION (The interpretative Study – Symbolic on the Campus Role, Al-Quran Islamic School and Custom Institution): The Islamic educational institutions need to be back and know the historical root to confirm the identity, character, distinctiveness and uniqueness. There is the timeless spirit to underlying model of ideal education in the contemporary era. The history of Islamiceducation was initiated by the trustees is a reflection of how Islam should be delivered. In the contemporary era of Indonesian Muslims, the spirit of Islamic education in the style of the trustees found that the momentum and the three existing educational institution are including schools, colleges, and traditional institutions. Those three institutions need the contextual efforts, synergies, and modifications to improve. If those systems in the three institutions have been connected, the epistemology of Islamic education Archipelago can be realized.